2016
DOI: 10.1103/physrevb.93.224415
|View full text |Cite
|
Sign up to set email alerts
|

Spin-orbit-coupling induced torque in ballistic domain walls: Equivalence of charge-pumping and nonequilibrium magnetization formalisms

Abstract: To study the effect of spin-orbit coupling (SOC) on spin-transfer torque in magnetic materials, we have implemented two theoretical formalisms that can accommodate SOC. Using the "charge-pumping" formalism, we find two contributions to the out-of-plane spin-transfer torque parameter β in ballistic Ni domain walls (DWs). For short DWs, the nonadiabatic reflection of conduction electrons caused by the rapid spatial variation of the exchange potential results in an out-of-plane torque that increases rapidly with … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 79 publications
3
11
1
Order By: Relevance
“…4(a)], β/α < +0.7-5 for ≈ 15 nm (C ⊥ tracks), and finally β/α ≈ −1 for ≈ 5 nm [out-of-plane magnetized (Ga,Mn)As]. Although this agrees with the tendency of the SOI-induced torques to increase with domain-wall width calculated in ballistic nickel domain walls [58], it disagrees with the prediction of Nguyen et al [20].…”
Section: B Spin-transfer-like Torquessupporting
confidence: 72%
See 1 more Smart Citation
“…4(a)], β/α < +0.7-5 for ≈ 15 nm (C ⊥ tracks), and finally β/α ≈ −1 for ≈ 5 nm [out-of-plane magnetized (Ga,Mn)As]. Although this agrees with the tendency of the SOI-induced torques to increase with domain-wall width calculated in ballistic nickel domain walls [58], it disagrees with the prediction of Nguyen et al [20].…”
Section: B Spin-transfer-like Torquessupporting
confidence: 72%
“…In metals it also covers the appearance of a DW resistance at abrupt interfaces [55][56][57][58], leading to a momentum transfer force [7,[59][60][61][62] never clearly identified experimentally [63]. Two contributions have been identified in the spin-relaxation nonadiabatic torque.…”
Section: B Spin-transfer-like Torquesmentioning
confidence: 94%
“…It has been recently shown that momentum scattering against defects and impurities has a dramatic impact on spin transport in any realistic magnetic textures [49,50]. As a matter of fact, since spin transport in magnetic textures presents striking similarities with spin transport in spin-orbit coupled band structures, momentum scattering breaking the coherent spin precession around the local magnetic field results, for instance, in an enhanced nonadiabaticity parameter [51].…”
Section: Robustness Of Topological Hall Signalsmentioning
confidence: 99%
“…The development of a new theoretical framework 32 for calculating magnetization damping and its implementation in the framework of density functional theory [33][34][35][36][37] has motivated systematic reinvestigation of the damping in alloys 38,39 and of the temperature dependence of damping in permalloy 40 allowing quantitative confrontation of theory and experiment without invoking adjustable parameters such as the relaxation time in the torque correlation method (TCM). [29][30][31]41 In this paper we describe in detail a method we recently used to calculate the resistivity ρ, spin flip diffusion length (SDL), and Gilbert damping parameter for Ni 1−x Fe x substitutional alloys, 33 the resistivity and damping for the itinerant ferromagnets Fe, Co and Ni with thermal disorder, 34 the resistance 42 and anisotropic damping 43 of magnetic domain walls, the nonadiabatic STTs in ballistic systems, 44 interface-enhanced damping, 45 thermal disorder effects in transport 46 and a novel interface spin Hall effect. 47 It extends earlier work [48][49][50] by including SOC and non-collinearity.…”
Section: Introductionmentioning
confidence: 99%